PENGEMBANGAN METODE KROMATOGRAFI CAIR KINERJA TINGGI UNTUK ANALISIS ASAM ASKORBAT DALAM SAMPEL PADAT YANG MENGANDUNG MG(II) DAN ZN(II) - Munigar, Milakanti
Background and purpose: Ascorbic acid is a compound that relatively unstable to heat, and environmental influences such as light, oxidator and metal ions. The use of ascorbic acid in combination with minerals in pharmaceutical products is likely to affect the stability of the ascorbic acid. Both Mg(II) and Zn(II) are metal ions that often used with ascorbic acid in the commercial products. In addition, the energy involvement in the product production processes such as grinding, mixing, granulation, compression and others are likely to affect the stability of ascorbic acid. The purpose of this research is to determine the effect of ascorbic acid grinding with and without Mg(II) and Zn(II) to the levels of ascorbic acid. Methods: Simulation samples were made with ascorbic acid grinded with and without Mg(II) or Zn(II) for 1 hour and samples were taken every 10 minutes. Ascorbic acid concentration measurements carried out using high performance liquid chromatography (HPLC) with methanol - 0.02 M phosphate buffer pH 2.8 (20:80) as mobile phase, C18 column, flow rate of 1 mL/min, temperature of 25°C, and X 244 nm. Results: Concentration levels decrease of grinded ascorbic acid with Mg(II) is 73.64%. Whereas grinded ascorbic acid with Zn(II) did not provide significant decline of concentration levels. Conclusion: Grinded ascorbic acid with Mg(II) showed a significant concentration levels decrease. Whereas grinded ascorbic acid with Zn(II) did not provide significant decline of concentration levels.